2022
DOI: 10.1177/03635465211067546
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Preoperative Patient Factors and Clinically Meaningful Outcomes After Hip Arthroscopy for Femoroacetabular Impingement Syndrome: A Machine Learning Analysis

Abstract: Background: The International Hip Outcome Tool 12-Item Questionnaire (IHOT-12) has been proposed as a more appropriate outcome assessment for hip arthroscopy populations. The extent to which preoperative patient factors predict achieving clinically meaningful outcomes among patients undergoing hip arthroscopy for femoroacetabular impingement syndrome (FAIS) remains poorly understood. Purpose: To determine the predictive relationship of preoperative imaging, patient-reported outcome measures, and patient demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 51 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…Within the field of hip arthroscopy several studies have now been performed that seek to predict patient-specific outcome following the procedure. Most have focused on patient reported outcome, with Kunze et al analysing single-surgeon data to predict multiple post-operative endpoints based on different outcome measuring tools [19][20][21][22]. The prediction of subsequent surgery following hip arthroscopy has also been performed by Haeberle et al based on another single-surgeon database of over 3000 patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Within the field of hip arthroscopy several studies have now been performed that seek to predict patient-specific outcome following the procedure. Most have focused on patient reported outcome, with Kunze et al analysing single-surgeon data to predict multiple post-operative endpoints based on different outcome measuring tools [19][20][21][22]. The prediction of subsequent surgery following hip arthroscopy has also been performed by Haeberle et al based on another single-surgeon database of over 3000 patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…In regards to age specifically, patients as young as 40 years old have been associated with worse outcomes in several studies. [21][22][23] In contrast, Griffin et al conducted a systematic review that found that 7 of 8 included studies reported good PROs for patients aged 40 or older. 45 Regarding isolated acetabuloplasty and short-term outcomes, Tjong et al found that there was no correlation between age and legacy scale PROs.…”
Section: Discussionmentioning
confidence: 99%
“…40, grade 0-I vs. grade II-IV). [21][22][23]26,27 Because age and OA are often interrelated, we attempted to evaluate the independent effect of each variable by subdividing the patients into four subgroups: (1) aged less than 40 and grade 0 to I, (2) aged 40 or greater and grade 0 to I, (3) aged less than 40 and grade II to IV, and (4) aged 40 or greater and grade II to IV. We also compared these two variables between patients that achieved favorable outcomes versus those that did not.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 Despite consistent improvements in PROs after hip arthroscopic surgery, meaningful improvements are negatively influenced by a greater BMI. 15 Furthermore, BMI has been established as a positive predictor of conversion to total hip arthroplasty (THA) after hip arthroscopic surgery. 10 This is a finding that has been consistently reported in the current literature.…”
mentioning
confidence: 99%